2017
DOI: 10.1073/pnas.1700561114
|View full text |Cite
|
Sign up to set email alerts
|

VAMP3 and SNAP23 mediate the disturbed flow-induced endothelial microRNA secretion and smooth muscle hyperplasia

Abstract: Vascular endothelial cells (ECs) at arterial branches and curvatures experience disturbed blood flow and induce a quiescent-to-activated phenotypic transition of the adjacent smooth muscle cells (SMCs) and a subsequent smooth muscle hyperplasia. However, the mechanism underlying the flow pattern-specific initiation of EC-to-SMC signaling remains elusive. Our previous study demonstrated that endothelial microRNA-126-3p (miR-126-3p) acts as a key intercellular molecule to increase turnover of the recipient SMCs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 36 publications
(39 reference statements)
5
33
0
Order By: Relevance
“…Previous studies have identified proteins that mediate regulated exocytosis in cardiomyocytes, such as VAMP3 [20], VAMP7/8 [21], and syntaxin [22]. Most of them belong to a superfamily of transmembrane proteins named SNAREs, which mediate the trafficking of cellular materials between intracellular compartments [23]. The SNARE protein VAMP3 is known to be involved in vesicle fusion and trafficking [24].…”
Section: Sarcolemmal and Intracellular Cd36 And Vamp3 Protein Contentmentioning
confidence: 99%
“…Previous studies have identified proteins that mediate regulated exocytosis in cardiomyocytes, such as VAMP3 [20], VAMP7/8 [21], and syntaxin [22]. Most of them belong to a superfamily of transmembrane proteins named SNAREs, which mediate the trafficking of cellular materials between intracellular compartments [23]. The SNARE protein VAMP3 is known to be involved in vesicle fusion and trafficking [24].…”
Section: Sarcolemmal and Intracellular Cd36 And Vamp3 Protein Contentmentioning
confidence: 99%
“…The essential (161) Qbc-SNARE SNAP23 is best known for its role in plasma membrane trafficking. SNAP23 mediates exocytosis in many cell types (109,110,174,178,219,234,256,312,346), for instance in neurons where it mediates the post-synaptic surface delivery of the glutamate receptor at dendritic spines (296). The Qb-and Qc-SNARE-motifs of SNAP23 are connected by a linker region containing five palmitoylated cysteines (272) that anchor it at the plasma membrane, recycling and late endosomes, and the trans-Golgi network (88,94,104,109,166,223,275,309,312,346).…”
Section: A Snap23mentioning
confidence: 99%
“…SNAP23 mediates exocytosis in many cell types (109,110,174,178,219,234,256,312,346), for instance in neurons where it mediates the post-synaptic surface delivery of the glutamate receptor at dendritic spines (296). The Qb-and Qc-SNARE-motifs of SNAP23 are connected by a linker region containing five palmitoylated cysteines (272) that anchor it at the plasma membrane, recycling and late endosomes, and the trans-Golgi network (88,94,104,109,166,223,275,309,312,346). SNAP23 is also found at phagosomes (38,51,79,215,221,271,286), and, although it might be recruited at several stages during phagosomal maturation (267), most quantitative proteomics show an overall decrease of phagosomal SNAP23 following uptake (FIGURE 5).…”
Section: A Snap23mentioning
confidence: 99%
See 1 more Smart Citation
“…SNARE proteins are considered to constitute the fusion machinery that draws two opposing membranes close together ( 66 ). Neuronal SNAREs including VAMP-2, SNAP-25A, and syntaxin-1A mediate miRNA exocytosis in neuroendocrine cells (Figure 1 A) ( 24 ), whereas VAMP-3 and SNAP-23 mediate secretion of vesicle-free miRNA in vascular endothelial cells ( 67 ). miRNA exocytosis is completely inhibited when neuronal SNAREs are absent in the in vitro reconstitution system, suggesting that neuronal SNAREs mediate the release of miRNAs in chromaffin cells ( 24 ).…”
Section: Mirna Exocytosis By Vesicle Fusionmentioning
confidence: 99%